On the damper cage of salient-pole synchronous generators - Nuzzo, Stefano (2018)
In the field of power generation, the wound-field synchronous generator has a well consolidated history of utilisation, mainly due to its proven and excellent performance. Nevertheless, due to the ever-increasing requirements in terms of power quality, efficiency, grid compliance and manufacturing costs, there is interest in renewing the design of this electrical machine, also allowed by the recent advancements in the computational resources. In this thesis, an unconventional, modulated damper cage topology for salient-pole synchronous generators is proposed in order to address the requirements inherent to the power quality (by improving the total harmonic distortion of the output voltage), the efficiency (by reducing the damper cage associated losses) and the manufacturing costs and times (by achieving an un-skewed stator core structure). In order to achieve these objectives, a suite of innovative modelling techniques are proposed and validated in this work, including hybrid numerical/analytical models, a new methodology to model skewing in an accurate and fast manner and specific optimisation methodologies for synchronous generators. In this work, these tools are then used to propose improvements to synchronous generators through new configurations of the damper winding. The thesis focuses on two main platforms, namely 1) a 4MVA generator, where the modulated damper bars are shown to improve the losses and the THD of the system and 2) a 400kVA generator, where it is shown how through a new damper winding configuration, the traditional skewing of the stator can be removed without compromising the machine performance in any way.